Clinical Benefits of Golden-Antrodia Camphorata Containing Antroquinonol in Liver Protection and Liver Fat Reduction After Alcoholic Hepatitis - Yen, Yu-Ting; Park, Joo-Hyun; Kang, Seung-Hyun; Su, Today; Cheng, Howard; Wen, Wu-Che; Lin, Shin-Shiou; Tai, Yu-Ling; Chen, Pei-Ni; Tsai, Shih-Chang (Frontiers in Pharmacology, 2022)
Objective: It has been reported that antroquinonol extracted from Golden-Antrodia camphorate exerts protective effects on liver function both in vitro and in vivo. However, the protective effects of Golden-Antrodia camphorata on liver function have not been fully investigated in human clinical studies. Therefore, the present study aimed to evaluate the beneficial effects of Golden-Antrodia camphorata on hepatic function after alcohol consumption in human subjects. Methods: A total of 80 participants with increased γ-glutamyl transferase levels (60-180 U/L) were enrolled in the current study and were randomly divided into two groups. Participants in the first group were orally administrated with 300 mg/day Golden-Antrodia camphorata (tablets), while those in the second group received placebo tablets for 12 weeks. Biochemical routine blood tests were performed at 6 and 12 weeks following the first administration. Results: At 12 weeks post the first Golden-Antrodia camphorata administration, the serum levels of aspartate aminotransferase (AST; P<0.0001), alanine aminotransferase (ALT; P=0.0002) and triglyceride (P=0.0158) were notably declined in the Golden-Antrodia camphorata treatment group compared with the placebo group. No clinically significant differences were observed between the Golden-Antrodia camphorata treatment and placebo groups in terms of general safety parameters. Conclusion: A statistically significant difference was obtained in the serum levels of AST, ALT and triglycerides between the Golden-Antrodia camphorata and placebo groups. However, no clinical significance was observed in any of the safety parameters examined. Overall, these findings indicated that treatment with Golden-Antrodia camphorata exerted protective effects on liver function.